f ( x + y ) = 3 y f ( x ) + 2 x f ( y )
Let f ( x ) be a function where f : R → R for which f ( 1 ) = 1 such that for all real x , y , the functional equation above satisfies.
Then find the value of f ( 2 0 ) − f ( 1 5 ) .
Note : To avoid tediousness, first generalize f ( x ) , then use a calculator to find the value asked.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Since we require values at only integral points, a much simpler approach would be to substitute x = n , y = 1 . This gives the following recursion f ( n + 1 ) = 3 f ( n ) + 2 n Which is simpler to solve or just compute.
It is given that: { f ( x + y ) = 3 y f ( x ) + 2 x f ( y ) f ( 1 ) = 1
⇒ { f ( n + 1 ) = 3 f ( n ) + 2 n f ( 1 ) = 3 f ( n ) + 2 n f ( 1 + n ) = 3 n f ( 1 ) + 2 f ( n ) = 3 n + 2 f ( n )
⇒ 3 f ( n ) + 2 n f ( n ) ⇒ f ( 2 0 ) − f ( 1 5 ) = 3 n + 2 f ( n ) = 3 n − 2 n = 3 2 0 − 2 2 0 − 3 1 5 + 2 1 5 = 3 4 7 1 4 1 9 6 8 6
Cool Solution + Nice approach an upvote given
Problem Loading...
Note Loading...
Set Loading...
Consider we substitute y to x and x to y.
f ( y + x ) = f ( x + y ) = 3 x f ( y ) + 2 y f ( x ) = 3 y f ( x ) + 2 x f ( y )
( 3 x − 2 x ) f ( y ) = ( 3 y − 2 y ) f ( x )
( f ( x ) 3 x − 2 x ) = ( f ( y ) 3 y − 2 y )
This relation has to be true for all x,y and since x,y are independent variables, so, these ratio have to be constant.
( f ( x ) 3 x − 2 x ) = C 1
f ( x ) = C ( 3 x − 2 x ) and from f ( 1 ) = 1 then C = 1
f ( x ) = ( 3 x − 2 x )
f ( 2 0 ) − f ( 1 5 ) = 3 2 0 − 2 2 0 − 3 1 5 + 2 1 5 = 3 4 7 1 4 1 9 6 8 6